Euro Area Policies : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
The euro area recovered from the economic doldrums. Executive Directors welcomed the recovery, supported by strong financial conditions, global growth, and improved financial positions. They encouraged the reformed Stability and Growth Pact over fiscal policies, and underscored the need for accelerated fiscal consolidation and structural reforms. They pointed to the integrated National Reform Programs under the reformed Lisbon process and labor market reforms. Directors welcomed the progress in integrating Europe's financial markets and the new Directive on Anti-Money Laundering and Combating the Financing of Terrorism.